PENERAPAN MODEL CIRC DENGAN MEDIA GAMBAR PERISTIWA DALAM PENINGKATAN KETERAMPILAN MENULIS PUISI PADA SISWA KELAS V SDN CANDIWULAN TAHUN AJARAN 2015/2016 - Purbandari, Shinta (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of CIRC Model Using Pictures of Event Media in Improving Poem Writing Skills for the Fifth Grade Students of SDN 1 Candiwulan in the Academic Year of 2015/2016. The objectives of this research is to improve poem writing skills on the application of CIRC model using pictures of event. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted of planning, action, observation, and reflection. The results of this research showed that the learning outcomes of poem writing skills increased. Techniques of collecting data were learning outcomes test, observation, and interview. Percentage of learning mastery in the first cycle was 46.66%, in the second cycle 70%, and in the third cycle 90%. The conclusion of this research is the application of CIRC model using pictures of event can improve poem writing skills for the fifth grade students SDN 1 Candiwulan in the academic year of 2015/2016.Keywords: CIRC, pictures of event, poem writing skillsAbstrak: Penerapan Model CIRC dengan Media Gambar Peristiwa dalam Peningkatan Keterampilan Menulis Puisi pada Siswa Kelas V SDN Candiwulan. Tujuan penelitian ini meningkatkan keterampilan menulis puisi dengan model CIRC dengan media gambar peristiwa. Penelitian ini merupakan Penelitian Tindakan Kelas Kolaboratif, tahapannya perencanaan, pelaksanaan, observasi, refleksi. Hasil penelitian menunjukkan bahwa ada peningkatan keterampilan menulis puisi dengan menerapkan model CIRC dengan media gambar peristiwa. Pengumpulan data dengan observasi,wawancara, dan tes. Persentase ketuntasan pada siklus I mencapai 46,66%, pada siklus II 70% dan siklus III 90%. Simpulan penelitian ini yaitu penerapan model CIRC dengan media gambar peristiwa dapat meningkatjan keterampilan menulis puisi pada siswa kelas V SDN Candiwulan tahun ajaran 2015/2016 Kata kunci: CIRC, Gambar Peristiwa, Keterampilan Menulis Puisi